2016
DOI: 10.1042/bst20150284
|View full text |Cite
|
Sign up to set email alerts
|

GPCR–styrene maleic acid lipid particles (GPCR–SMALPs): their nature and potential

Abstract: G-protein-coupled receptors (GPCRs) form the largest class of membrane proteins and are an important target for therapeutic drugs. These receptors are highly dynamic proteins sampling a range of conformational states in order to fulfil their complex signalling roles. In order to fully understand GPCR signalling mechanisms it is necessary to extract the receptor protein out of the plasma membrane. Historically this has universally required detergents which inadvertently strip away the annulus of lipid in close … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…In the SMALP eld, it's recently been shown that GPCRs exhibit higher activity in vitro when extracted with SMA system as compared to detergent isolation methods, supporting the hypothesis that preservation of the native membrane environment inuences activity of membrane bound proteins. 48,66,71 The SMA buffer used in this study (pH ¼ 9.5), lack of divalent ions and high monovalent ionic strength (125 mM KCl), make this buffer system non-physiological for most proteins. Beyond that, it makes the direct comparison of DDM and SMA extracted proteins in certain downstream analyses difficult, as seen in our P700 + reduction kinetics (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In the SMALP eld, it's recently been shown that GPCRs exhibit higher activity in vitro when extracted with SMA system as compared to detergent isolation methods, supporting the hypothesis that preservation of the native membrane environment inuences activity of membrane bound proteins. 48,66,71 The SMA buffer used in this study (pH ¼ 9.5), lack of divalent ions and high monovalent ionic strength (125 mM KCl), make this buffer system non-physiological for most proteins. Beyond that, it makes the direct comparison of DDM and SMA extracted proteins in certain downstream analyses difficult, as seen in our P700 + reduction kinetics (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The styrene-maleic acid (SMA) copolymer has recently gained much attention as solubilizing agent in the field of membrane protein and lipid bilayer research (for reviews, see Dörr et al (1), Lee et al (2), and Wheatley et al (3)). It has been shown that this polymer is able to directly solubilize lipid membranes into nanodisk particles without the help of detergents.…”
Section: Introductionmentioning
confidence: 99%
“…1,2-Dimyristoylsn-glycero-3-phosphocholine (di-14:0 PC) is selected as lipid because it has been used in different SMA studies where the mode of action of SMA (3,15) and the structural properties of styrene maleic acid lipid particles (14) have been characterized in molecular detail. In the systematic comparison presented here, we focus on different steps in the solubilization process of lipid membranes by SMA according to our previously proposed model (15).…”
Section: Introductionmentioning
confidence: 99%
“…Characterizing the function of membrane receptors like GPCRs can be achieved with binding assays, which are possible in SMALPs [18,41]. For channels and transporters it relies on measuring changes in the concentration of the substrate on either side of the protein, which generally requires reconstitution of the protein into proteoliposomes or another bilayer system.…”
Section: Lack Of Sidedness and Need For Reconstitutionmentioning
confidence: 99%